Pengembangan Kompetensi Guru PAUD Menciptakan Digital Picture Storybook Digital Berbasis Artificial Intelligence di Kiddos Smart School - Juanda, Juanda; Haripuddin, Haripuddin; Azis, Azis (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Teachers at Kiddos Smart School Makassar faced challenges in exploring children's literature and integrating Artificial Intelligence (AI) technology into the creation of digital picture storybooks. This Community Service Program aims to enhance teachers' abilities in creating interactive AI-based learning media in early childhood. The implementation methods include training, workshops, and intensive mentoring on using tools like ChatGPT, Canva Magic Media, and Suno.ai to create digital text, illustrations, and background music. As a result, teachers were able to adapt children's literature elements into engaging digital narratives and improve their technical skills in producing AI-based digital media. This Community Service Program successfully strengthened teachers' capacity to integrate AI technology, which is expected to enhance educational quality and cognitive development in children.